PENGARUH VARIASI DOSIS BEKAS MAGGOT (Hermetia illucens) TERHADAP PERTUMBUHAN TANAMAN KALE (Brassica oleracea var. Acephala) UNTUK PENYUSUNAN LKPD PERTUMBUHAN DAN PERKEMBANGAN KELAS XII SMA - Dhani Sakhiri; Suharno Zen; Agus Sutanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2024)
Maggot scum is a by-product of the maggot cultivation process (Hermetia illucens). Maggot can be used as organic fertilizer because it contains some nutrients needed by plants such as nitrogen, phosphorus, and also potassium. The objectives of this study are 1) to determine whether there is an effect of giving varying doses of ex-maggot (Hermetia illucens) on the growth of kale plants (Brassica oleracea var. Achepala), 2) to determine the best treatment of giving varying doses of ex-maggot (Hermetia illucens) on the growth of kale plants (Brassica oleracea var. Achepala), 3) to develop learning resources in the form of Learner Worksheets on class XII Senior High School growth and development material. This research is an experimental research using the Complete Randomized Design method. In the research conducted, there were 1 control and 3 treatments with dose information, control (only soil), treatment 1 (100 g of ex-maggot), treatment 2 (200 g of ex-maggot), and treatment 3 (300 g of ex-maggot). The growth parameters of kale plants (Brassica oleracea var. Achepala) observed were plant height, number of leaves (strands), and wet weight of kale plants (Brassica oleracea var. Achepala). Based on the results of the research and ANOVA test, there is an effect of giving variations in the dose of former maggot on the growth of kale plants (Brassica oleracea var. Achepala). The further test used gives the result that the variation of the dose of ex-maggot 300 grams are the best treatment that gives effect to the growth of kale plants (Brassicca oleracea var. Achepala). The results of this study can also be used as a biology learning resource in the form of Learner Worksheet class XII Senior High School growth and development material.